A Variant of Gorlin–Goltz Syndrome with Synchronous Malignant and Multiple Benign Lesions of the Jaws - A Case Report - Reena R. John; Pavithran Ashokkumar; Kathirvel Gopalakrishnan; Mohithan Subramanian (Indian Journal of Dental Research)
Introduction: Although numerous syndromic and non-syndromic odontogenic lesions of the jaws have been documented in the literature, there are very few cases of simultaneous benign and malignant jaw lesions. Patient Concerns: We present a case of right maxillary squamous cell carcinoma along with several benign odontogenic cystic lesions of the jaws and skeletal abnormalities that meet the criteria for Gorlin-Goltz syndrome. Take-Away Lessons: With a review of the literature, the specifics of management and follow-up are discussed.